2021
DOI: 10.4187/respcare.09191
|View full text |Cite
|
Sign up to set email alerts
|

Awake Prone Positioning in Non-Intubated Patients With Acute Hypoxemic Respiratory Failure Due to COVID-19

Abstract: B Background Awake prone positioning (APP) has been advocated to improve oxygenation and prevent intubations of patients with acute hypoxemic respiratory failure due to coronavirus disease 2019 . This paper aims to synthesize the available evidence on the efficacy of APP.Methods: We performed a systematic review of proportional outcomes from observational studies to compare intubation rate in patients treated with APP or with standard care.Results: A total of 46 published and 4 unpublished observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
1
35
1
2
Order By: Relevance
“…Prone position is a position in which the patient is treated by remaining prone without endotracheal intubation. Some studies have found that for severe patients, prone position combined with mask oxygen or HFNC or non-invasive positive pressure ventilation can reduce the probability of endotracheal intubation and ultimately reduce patient mortality [38][39][40][41][42]. Other studies have shown that prone position may be more effective when performed early than later [10,43].…”
Section: Discussionmentioning
confidence: 99%
“…Prone position is a position in which the patient is treated by remaining prone without endotracheal intubation. Some studies have found that for severe patients, prone position combined with mask oxygen or HFNC or non-invasive positive pressure ventilation can reduce the probability of endotracheal intubation and ultimately reduce patient mortality [38][39][40][41][42]. Other studies have shown that prone position may be more effective when performed early than later [10,43].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The need for tracheal intubation in hospitalised COVID-19 patients is reported as high as 27%-30% in observational studies, with great heterogeneity across studies. 4 The rate of intubation in COVID-19 patients with non-severe respiratory failure who initially need only standard oxygen therapy is difficult to estimate with the available literature. Among treatment strategies that have been tested or advocated for COVID-19 patients, awake prone positioning is a simple and safe technique which merits further investigations.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 1–3 The need for tracheal intubation in hospitalised COVID-19 patients is reported as high as 27%–30% in observational studies, with great heterogeneity across studies. 4 The rate of intubation in COVID-19 patients with non-severe respiratory failure who initially need only standard oxygen therapy is difficult to estimate with the available literature.…”
Section: Introductionmentioning
confidence: 99%
“… [21] Seven currently available meta-analyses have concluded that APP improves oxygenation in patients with COVID-19-induced acute hypoxemic respiratory failure. [22] , [23] , [24] , [25] , [26] , [27] , [28] …”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , [30] , [31] , [32] ] The largest randomized evidence published as an international multi-centered meta-trial, including patients hospitalized with acute hypoxemic respiratory failure due to COVID-19 pneumonia and requiring HFNC treatment, has demonstrated that APP significantly reduced the risk of intubation by 7%. [21] Moreover, meta-analyses and systematic reviews of non-randomized controlled studies have also shown the effect of APP on reducing the risk of intubation, [22] except for a meta-analysis conducted by Pavlov et al [25] at early pandemic, and including only observational studies. [27] The introduction of randomized controlled studies offsets this effect.…”
Section: Introductionmentioning
confidence: 99%